Understanding energy production mechanisms in middle-distance running - Jiamin, H. (New Studies in Athletics, 2015)
Research findings about energy production in the middle-distance races vary significantly. Some authors think middle-distance running is aerobic dominated and training should be focused in this direction while others have reached the opposite conclusion and that training should have an anaerobic focus. From the coaching practice perspective, a decision has to be made about what type of training is right for athletes aiming for success in these events. This article reviews recent literature on the topic and provides observations that may be valuable for coaches working with middle-distance runners. After summarising the main findings the author explains the differences between the subjects and in approaches taken by the studies in question. He concludes that 1) coaches should analyse the energy contribution balance for each individual athlete and 2) it may be more meaningful to do targeted anaerobic/aerobic training for each section of the race, rather than using one approach for the whole race.